A neglected causative agent in diabetic foot infection: a retrospective evaluation of 13 patients with fungal etiology - ÖZTÜRK, Anıl Murat (Turk J Med Sci, 2019)
BACKGROUND/AIM: Clinicians often neglect fungal infections and do not routinely investigate deep tissue from the wound for fungal culture and sensitivity due to insufficient information in the literature. In this study, we aimed to evaluate fungal etiology of invasive fungal diabetic foot which is rarely reported in the literature. MATERIALS AND METHODS: The patients who were unresponsive to antibiotic therapy and those with positive fungal in bone or deep tissue culture were enrolled in the study. Detailed hospital records were retrieved for demographics and clinical features. RESULTS: A total of 13 patients who were diagnosed with invasive fungal diabetic foot (ten females, three males, mean age 59.8 ± 9 years) were included. All of the patients had type-2 diabetes mellitus. Eleven (84.6%) patients had mixed infection. The most common cause of fungal infections of diabetic foot ulcers was the Candida species. Ten (76.9%) patients underwent amputation, two (15.4%) patients refused amputation, and one patient died before surgery. CONCLUSION: Invasive fungal infections may also be a causative pathogen in deep tissue infections. Therefore, fungal pathogens should be considered in patients unresponsive to long-term antibiotic therapy. Early detection of fungal infections in high-risk individuals is critical for the prevention of severe consequences such as foot amputation.